Revitalizing Science Education in Ethiopia: Analyzing the Causes and Solutions for Declining Enrollment in Physics, Chemistry, and Mathematics - Belay Sitotaw Goshu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2025)
The decline in enrollment and performance in natural science disciplines (physics, chemistry, and mathematics) within Ethiopian public universities is linked to significant motivational challenges among instructors. This study aims to identify the underlying factors contributing to these challenges, focusing on political barriers, delayed rank promotions, and the absence of financial incentives. A mixed-method approach was used, incorporating survey data from 150 instructors and 30 university administrators, alongside document analysis of institutional policies. The survey revealed that 72% of respondents identified delayed promotions as a major demotivating factor, while 65% reported the absence of incentives as a critical issue. Statistical analysis indicated a strong negative correlation (r = -0.78, p < 0.05) between instructor motivation and the perceived impact of political barriers on professional growth. Administrators acknowledged these challenges but cited systemic issues such as limited funding and political constraints. The findings highlight that insufficient motivation among instructors affects student learning outcomes and engagement with science subjects. The study concludes with recommendations for establishing transparent promotion systems, introducing financial incentives, and increasing government investment in higher education. Implementing these measures would enhance faculty motivation, support innovative teaching and research, and ultimately improve student interest and performance in the natural sciences.